Evaluation of biodegradability of waste before and after aerobic treatment = Ocean podatności na rozkład biologiczny odpadów przed i po tlenowym przetworzeniu - Suchowska-Kisielewicz, Monika; Jędrczak, Andrzej; Sadecka, Zofia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An important advantage of use of an aerobic biostabilization of waste prior to its disposal is that it intensifies the decomposition of the organic fraction of waste into the form which is easily assimilable for methanogenic microorganisms involved in anaerobic decomposition of waste in the landfill.
Keywords: tlenowe przetworzenie odpadów; produkcja biogazu; odpady komunalne; rozkład biologiczny odpadów; aerobic pre-treatment of waste; biodegradability of waste landfills; biogas production; municipal solid waste